Increased levels of soluble corin in pre-eclampsia and fetal growth restriction. (December 2016) - Miyazaki, Jun; Nishizawa, Haruki; Kambayashi, Asuka; Ito, Mayuko; Noda, Yoshiteru; Terasawa, Sumire; Kato, Takema; Miyamura, Hironori; Shiogama, Kazuya; Sekiya, Takao; Kurahashi, Hiroki; Fujii, Takuma
Abstract: Atrial natriuretic peptide is biologically activated by the atrial natriuretic peptide-converting enzyme, corin, and has an important role in regulating blood pressure. We detected elevated serum corin levels in women with pre-eclampsia. Interestingly, the serum corin levels were also found to be elevated in pregnancies with a related disorder, unexplained fetal growth restriction (FGR) without hypertension, suggesting that this phenomenon is not simply a response to maternal hypertension. CORIN mRNA levels were not elevated in placentas from pre-eclampsia or unexplained FGR cases. Likewise, similar signal intensities were found for corin in placental syncytiotrophoblast cells by immunostaining. In contrast, corin signals were higher in maternal decidua cells from pre-eclampsia and unexplained FGR cases. These data suggest that corin may be upregulated in maternal decidua in response to an etiologic pathway that is common to pre-eclampsia and FGR. Highlights: We evaluated the expression of corin in pre-eclampsia and FGR without hypertension. Corin was upregulated in maternal serum and decidua not only in pre-eclampsia but also FGR. Up-regulation of the decidual corin might play an etiologic role in pre-eclampsia and FGR.